Antibiotic resistance and heavy metal tolerance plasmids: The antimicrobial bulletproof properties of escherichia fergusonii isolated from poultry - Galetti, Renata; Filho, Rafael Antonio Casarin Penha [UNESP]; Ferreira, Joseane Cristina; Varani, Alessandro M. [UNESP]; Darini, Ana Lúcia Costa (Taylor & Francis, 2019)
We describe the mobilome of Escherichia fergusonii 40A isolated from poultry, consisting of four different plasmids, p46_40A (IncX1, 45,869 bp), p80_40A (non-typable, 79,635 bp), p150_40A (IncI1-ST1, 148,340 bp) and p280_40A (IncHI2A-ST2, 279,537 bp). The mobilome-40A carries a blend of several different resistance and virulence genes, heavy metal tolerance operons and conjugation system. This mobilome 40A is a perfect tool to preserve and disseminate antimicrobial resistance and makes the bacterial isolate incredibly adapted to survive under constant antimicrobial pressure.
Keywords: Antibiotic resistance; Heavy metal tolerance; Plasmids; Poultry